Reviewers For Vol 15 No. 1 - Editor (BIOTROPIA, 2008)
Prof. Dr. Mirnawati Sudarmanto, Faculty of Veterinary Medicine, Bogor Agricultural University, Bogor (IPB), Indonesia Dr. Ratih Dewanti Hariyadi, Faculty of Agricultural Technology, Bogor Agricultural University (IPB), Bogor, Indonesia Prof. Dr. M.A. Chozin, Faculty of Agriculture, Bogor Agricultural University (IPB), Bogor, Indonesia Dr. Soekisman S. Tjitrosemito, Faculty of Mathematics and Natural Sciences, Bogor Agricultural University (IPB), Bogor, Indonesia Dr. Dahlia Sukma, Faculty of Mathematics and Natural Sciences, The State University of Jakarta (UNJ), Jakarta 13220, Indonesia Dr. Lisdar M. Sudirman,Â  Faculty of Mathematics and Natural Sciences, Bogor Agricultural University (IPB), Bogor, Indonesia Dr. Nurita L. Toruan-Mathius, Tissue Culture Laboratory, SMART Research Institute (SMARTRI), Bogor, Indonesia Ir. Soemaryono M.Sc., Biotechnology Research Unit For Estate Crops, Bogor, Indonesia Dr. Okky S. Dharmaputra, SEAMEO BIOTROP/Faculty of Mathematics and Natural Sciences, Bogor Agricultural University (IPB), Bogor, Indonesia Dr. Gayuh Rahayu, Faculty of Mathematics and Natural Sciences, Bogor Agricultural University (IPB), Bogor, Indonesia Dr. Yadi Haryadi, Faculty of Agricultural Technology, Bogor Agricultural University (IPB), Bogor, Indonesia Dr. Zainal Mahmud, Indonesian Agency for Agricultural Research and Development (Puslitbangbun), Bogor, IndonesiaÂ